Solicitor-client privilege - Dodek, Adam (LexisNexis Canada, 2014)
"Solicitor-Client Privilege is the only Canadian textbook of its kind to explain key aspects of lawyer-client confidentiality. With a Foreword written by former Supreme Court of Canada justice Ian Binnie, this distinctly Canadian law textbook analyzes the exceptions to privilege, conditions where privilege is unclear, and situations of competing interests that might bring into question the application of privilege. Especially useful is the examination of privilege in specific contexts, such as in civil litigation, administrative law, corporate settings, and government. Portable and immediately accessible, this useful hardcover book gives lawyers the answers they quickly need, and assurances as to when they can rely on solicitor-client privilege and when they can challenge it."–Publisher's description.